2007
DOI: 10.1111/j.1365-2672.2007.03344.x
|View full text |Cite
|
Sign up to set email alerts
|

In vitrobiofilm model for studying tongue flora and malodour

Abstract: Aims:  To develop a perfusion biofilm system to model tongue biofilm microflora and their physiological response to sulfur‐containing substrates (S‐substrates) in terms of volatile sulfide compound (VSC) production. Methods and Results:  Tongue‐scrape inocula were used to establish in vitro perfusion biofilms which were examined in terms of ecological composition using culture‐dependent and independent (PCR‐DGGE) approaches. VSC‐specific activity of cells was measured by a cell suspension assay, using a portab… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(22 citation statements)
references
References 26 publications
1
21
0
Order By: Relevance
“…The perfusion biofilm system (see Figure ) incorporating a tongue‐derived microflora (i.e. microcosm in the form of biofilm cells) has been used to study the collective biofilm physiological response to sulfur‐containing substrates (S‐substrates) in terms of VSC production . Biofilms were examined in terms of ecological composition using culture‐dependent and independent (PCR‐DGGE) approaches.…”
Section: In Vitro Modelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The perfusion biofilm system (see Figure ) incorporating a tongue‐derived microflora (i.e. microcosm in the form of biofilm cells) has been used to study the collective biofilm physiological response to sulfur‐containing substrates (S‐substrates) in terms of VSC production . Biofilms were examined in terms of ecological composition using culture‐dependent and independent (PCR‐DGGE) approaches.…”
Section: In Vitro Modelsmentioning
confidence: 99%
“…The flat‐bed perfusion biofilm matrix was inoculated from a tongue biofilm sample (taken from one individual volunteer). One‐fifth strength brain heart infusion broth supplemented with haemin (0.0001%), cysteine (0.01% w/v) and di‐thiothreitol (0.005% w/v) and adjusted to pH 7.2 (± 0.2 units) was perfused into the matrix at a flow rate of 20 ml/h for 48 h to allow colonization and maturing of the biofilm to reach steady‐state, as determined in previous experiments . The biofilm module (see Figure ) was incubated at a temperature of 36°C ± 1°C and the gas flow rate (N 2 /CO 2 , 95/5 v/v%) was set at 50 ml/h.…”
Section: In Vitro Modelsmentioning
confidence: 99%
“…Wirthin et al [53] demonstrated that only after 100 h incubation time the steady state was reached. Despite the quantitative increase some authors consider biofilms after 48 h or even less incubation time as sufficient for routine experiments [8], [23], [46], [58], [66], [67]. A cell culture period of 72 hours is advantageous though, since resistance against antimicrobial agents was at its maximum after 72 h [64], [68] and the plaque milieu only becomes caries-producing after 72 h [1], [6], [39], [69], [70].…”
Section: Discussionmentioning
confidence: 99%
“…From appropriate dilutions, 0.1 ml of the aliquot was spread plated on Plate Count Agar (PCA) and the plates were incubated at 35°C for 24 h. After incubation, plates with colonies between 30 and 300 were counted to estimate the abundances of aerobic mesophilic bacteria (AMB) [8]. Similarly, the diluents were spread-plate on Salmonella Shigella Agar (SSA), Xylose Lysine Deoxycholate (XLD) Agar, Eosin Methylene Blue (EMB) Agar, MacConkey (MAC) agar and incubated at 37°C for 24 h. After which, different types of colonies of bacteria with different colors like pink to red purple colonies on EMBA, Red to Black centered colonies on SSA and XLD Agar were counted as member of a family of Enterobacteriaceae [9]. A purplish colony surrounded by reddish zone on MAC agar and Metallic green sheen on EMB Agar were counted as Coliforms [8].…”
Section: Estimation Of Cultivatable Bacterial Loadmentioning
confidence: 99%